Reflection of the community participation in enhancing organizational excellence - Rumaid, Jinan Jassim; Ismail, Firas Muhammad (Journal of Economics and Administrative Sciences, 2020)
The research aims to identify the role of community participation in achieving organizational distinction in the Dhulia’s municipality, which is one of the formations of the Ministry of Construction, Housing, Municipalities and Public Works in Salah al-Din Governorate, which is one of the service organizations that have a fundamental role in providing service to the community, which has faced many administrative challenges and many problems caused by the rapid and continuous changes in the environment, therefore modern management concepts must be adopted, such as community participation and the knowledge of its role To achieve its goals, which helps it in facing changes as well as achieving organizational excellence. An analytical descriptive approach was used, so the research sample consisted of (83) individuals and the sample was chosen by using a comprehensive inventory, The research evidence was obtained by relying on the questionnaire, which was prepared from ready-made measures from foreign studies and was subjected to tests of validity and reliability, with using of statistical tests, including arithmetic mean, standard deviation, percentage and iterations and Pearson correlation coefficient, simple linear regression Based on the statistical program (SPSS. V.25) for testing the validity of the hypotheses. The research reached a set of conclusions, including that the level of societal participation and organizational excellence in the researched organization was at the high degree to the two variables and that the inclusiveness dimension has a strong impact of which is one of the dimensions of societal participation in organizational excellence. Enhancing the community participation in Dhulia’s municipality will contribute to enhancing leadership and employee development, improving the current policy and strategy, and strengthening relationships and resources, and Enriching the literature on organizational behaviour and contributing to research on how community participation contributes to achieving organizational excellence.